Green reduction of ZnO nanoparticles using cationic dialdehyde cellulose (cDAC) for efficient Congo red dye removal - Tolosa, Gabrieli Roefero [UNESP]; Gomes, Andressa Silva [UNESP]; Leal, Maria Vitória Guimarães; de Oliveira Setti, Grazielle [UNESP]; Dognani, Guilherme [UNESP]; Job, Aldo Eloízo [UNESP] (Elsevier, 2024)
More sustainable materials have been becoming an important concern of worldwide scientists, and cellulosic materials are one alternative in water decontamination. An efficient strategy to improve removal capacity is functionalizing or incorporating nanomaterials in cellulose-based materials. The new hybrid cDAC/ZnONPs was produced by green synthesis of zinc oxide nanoparticles (ZnONPs), promoting the in situ reduction and immobilization on the cationic dialdehyde cellulose microfibers (cDAC) surface to remove Congo red dye from water. cDAC/ZnONPs was characterized by scanning electron microscopy (SEM-EDS) and infrared spectroscopy (FTIR), which showed efficient nanoparticles reduction. Adsorption efficiency on cationic cellulose surface was investigated by pH, contact time, initial concentration, and dye selectivity tests. The material followed the H isotherm model, which resulted in a maximum adsorption capacity of 1091.16 mg/g. Herein, was developed an efficient and ecologically correct new adsorbent, highly effective in Congo red dye adsorption even at high concentrations, suitable for the remediation of contaminated industrial effluents.
Keywords: Biosorption; Cationic Dialdehyde cellulose; Congo red; Dyes removal; Water decontamination; Zinc oxide nanoparticles